KESIAPAN GURU DALAM MENERAPKAN KURIKULUM MERDEKA DI SDIT ARRABANI PEKANBARU (TANTANGAN DAN STRATEGI) - Diffa Pebriani; Radhiyatul Fithri; Sakban; Yesika Novita Rahmi (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
Teachers have a very crucial position in the education process. They also function as supporters for students. The main task of teachers is to educate, teach, guide, train, assess, and monitor students. In addition, teachers have an important responsibility in developing the curriculum, namely determining the direction and objectives of the lessons taught, as well as designing strategies to develop, evaluate, and compile a curriculum that is in accordance with the learning needs and characteristics of students. Because of this important role, teachers need to be ready to implement the independent curriculum. The purpose of this study was to find out. 1.) How is the readiness of teachers at SDIT Arrabani Pekanbaru in implementing the Independent Curriculum? 2.) What are the challenges and difficulties faced by teachers at SDIT Arrabani Pekanbaru in implementing the independent curriculum? This researcher applies a qualitative approach with a phenomenological research type. This study focused on the principal of SDIT Arrabani Pekanbaru, the deputy head of curriculum, and teachers for grades 1 to 4 at SDIT Arrabani Pekanbaru through data collection techniques that include interviews, observations, and documentation. The collected data is then analyzed through the following steps: 1) data collection, 2) data reduction, 3) data presentation, 4) drawing conclusions.